a Kajian Naratif Pengukuran Kualitas Peresepan Pasien Diabetes Mellitus Lanjut Usia - Fisia Niti Admadja; Yosi Irawati Wibowo; Karina Kumaladewi Widjaja; Adji Prayitno Setiadi (Jurnal Farmasi Indonesia, 2023)
The aging populations has increased worldwide, resulting in higher prevalences of non-communicable diseases, including Diabetes Mellitus (DM). Elderly with DM requires long-term prescribing which warrants special considerations. Hence, this narrative review aims to identify quality measurement tools and quality prescribing in elderly patients with DM. This review included literature searching in three databases [i.e., Pubmed (MEDLINE), Science Direct, and CINAHL] with combination of keywords: (Diabetes) AND (Elderly OR older OR geriatric) AND (“Potentially inappropriate medication” OR “potentially inappropriate prescribing” OR “inappropriate prescribing” OR “quality prescription” OR “rational prescribing”). The searching resulted in 1059 articles; and after the selection process, 10 articles were included in this study. The extracted data indicated that tools with explicit criteria (such as Beer's Criteria) were more commonly used to measure quality prescribing in elderly patients with DM compared to those with implicit criteria (i.e., Prescribing Quality Assessment Checklist) (9 articles versus 1 article, respectively). Varying quality prescribing were reported dependent on the tools used. The percentage of Potentially Inappropriate Medication (PIM) measured using explicit tools ranged from 22,7% to 68,1%; glibenclamide or glyburide were among the most common PIM. Whereas, 83.2% of precriptions measured with the implicit criteria in one article indicated poor quality. This finding demonstrated the needs of strategy to improve the quality of prescribing in elderly patients with DM.